Transition programs for children and youth with diverse needs - Scorgie, Kate; Forlin, Chris (Bingley, U.K. : Emerald Publishing Limited, 2022)
Volume 18 of International Perspectives on Inclusive Education offers multiple international perspectives on transitions for children and youth with diverse backgrounds and special needs. Transition approaches are viewed from early childhood through to post-secondary and into workplace settings using a unique convergence of integrating research and practice in schools, workplaces, organizations, and communities. Effective evidence-based programs, interventions, and strategies are also incorporated throughout, with a strong emphasis on collaborative partnerships underpinning all aspects of transition. This research is predicated on the assumption that inclusion in academic, social, vocational, and other contexts incorporates all stakeholders. Providing a focus on meaningful involvement and participation in communities and activities of choice, that secure benefits for all, the chapter authors examine both innovative evidence-based practices that facilitate transition, and potential barriers, supplemented by informative case studies. In addition to providing knowledge and skill training for establishing effective transitions, this volume views programs, attitudes, expectations, and perceptions, in relation to what it means to be accorded welcome into a particular setting.
Section 1. Transitions to and through schooling for ece / Primary / Elementary -- Chapter 1. Exhausted, scared, anxious, stressed, frustrated, sad; but hopeful: Transitioning two boys with autism from home to school / Emma Barrett -- Chapter 2. The 'now what dilemma': An emirati perspective on issues related to transition of learners with send from early care to primary education / Rawhi Abdat and Eman Gaad -- Chapter 3. Framing the foundations: A practice model for teaching children on the autism spectrum in early years classrooms / Wendi Beamish and Annalise Taylor -- Chapter 4. The experiences of first-generation learners during transition from a government school to a private inclusive school in a tribal region of maharashtra, India / Ratika Malkani and Richard Rose -- Section 2. Transitions to and through schooling for secondary -- Chapter 5. A journey to belonging: Transitioning through school with autism / Annetta Galer -- Chapter 6. Transition from primary to secondary school: A collaborative intervention between six South African schools situated in socio-economically challenged contexts / Ansie Elizabeth Kitching, Robert Tubb Carstens, and Petra Engelbrecht -- Chapter 7. Transitioning from special schools or settings into inclusive schools: Expectations and realities for students with complex needs / Chris Forlin and Jo Deppeler -- Chapter 8. 'It doesn't just happen': Transforming schools for effective transition / Michelle Ralston and Kerry Dally -- Chapter 9. Genuine engagement with children: A principal's reflection on creating a learning environment where equity is upheld, and diversity embraced / Simon Reid -- Section 3: Transition to post-secondary education and vocational opportunities -- Chapter 10. Career interventions with an inclusive perspective for individuals with disabilities and vulnerabilities / M. Cristina Ginevra, Sara Santilli, Ilaria Di Maggio, and Laura Nota -- Chapter 11. Falling between two stools? Post-secondary transition planning for students with intellectual disabilities in the republic of Ireland / Joanne Banks, Des Aston, and Michael Shevlin -- Chapter 12. Preparing students to transition to employment: Teacher perspectives and student outcomes of the California workability 1 program / Tamai Johnson -- Chapter 13. The regional learning collaborative: Supporting successful transitions to and through college for all students / Nazanin Zargarpour and Susan R. Warren -- Chapter 14. Transitioning dreams to reality: Inclusive post-secondary education at concordia university of edmonton / Barbara Van Ingen, Brent Bradford, Patricia Bowman, Bruce Uditsky, Jaime Skidmore, and Sarah Pereira -- Section 4: Collaborative programs, partnerships and resources for transition -- Chapter 15. Circles: A three-team interagency collaboration approach to support successful transitions for students with disabilities / Stephen M. Kwiatek, Valerie L. Mazzotti, Jared. H. Stewart-Ginsburg, and Janie N. Vicchio -- Chapter 16. Advancing school to work transition programs for students with disabilities in indonesian special schools / Nur Azizah -- Chapter 17. Barriers to community re-entry for incarcerated youth: Stakeholders' perspectives in australia and the United States / Iva Strnadová, Heather Griller Clark, Sue C. O'neill, Therese M. Cumming, Sarup R. Mathur, Timothy C. Wells, and Joanne Danker -- Chapter 18. Libraries as social agencies and transition points: Serving diverse populations / Maria Pacino -- Chapter 19. Collaborative partnerships and strategies to promote effective transitions and support for students with disability: The role of parent groups in malawi / Msenga Anyelwisye Mulungu.
Includes index.
Includes bibliographical references.
Keywords: Students, Transfer of; Students with disabilities -- Services for; Inclusive education; Education -- Inclusive Education; Teaching of specific groups & persons with special educational needs